Penerapan Disgorgement Fund Sebagai Upaya Memberikan Perlindungan Bagi Investor Di Pasar Modal Indonesia - Aryansyah, Rezza; Nefi, Arman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This journal discusses the implementation of the Disgorgement Fund as an effort to provide protection for investors in the Indonesian capital market as outlined in POJK No. 65/POJK.04/2020 concerning Return of Illegal Profits and Investor Loss Compensation Fund in the Capital Market Sector. The issues raised are how to implement the Disgorgement Fund itself in Indonesia and analyze the advantages and disadvantages of implementing the Disgorgement Fund in Indonesia in an effort to provide protection to investors in Indonesia. In its implementation, the Disgorgement Fund can calm investors while minimizing the crime rate in the Indonesian capital market so that the integrity of the capital market can be maintained, even though there are weaknesses such as parties subject to illegal return of profits that can harm investors and the difficulty of proving crimes in the capital market. But with the disgorgement fund system, that is effective, proportional, and preventive so that it can make a party choose not to commit a violation. Returning illegal profits as a remedial action is expected to prevent parties who commit violations from enjoying the profits they have obtained illegally, compensate for losses from victims of violations, contain corrective elements, and are expected to provide a deterrent effect.